Impact of sodium alginate gelling and ingredient amalgamating order on ingredient interactions and structural stability of ice cream. (July 2021) - Goraya, Rajpreet Kaur; Singla, Mohit; Bajwa, Usha; Kaur, Amarjeet; Pathania, Shivani
Abstract: The impact of ingredient amalgamating order on the physicochemical properties, sensory, microscopic, and melting characteristics of ice cream was studied. The pre-treatment step involved sodium alginate hydrated in water (SW) and milk (SM). Control (C) sample was developed using standard dairy-based ice cream mix formulation technique whereas SW and SM samples were further mixed with the milk and order of addition of dry ingredients prior to butter addition (SW1, SM1) was compared to the samples in which butter was added before dry ingredients inclusion (SW2, SM2). It was observed that the consistency and structural characteristics of ice cream samples were significantly influenced by pre-treatment and treatment steps. SM1 sample exhibited maximum viscosity; however, SM2 was the most stable formulation with the highest first drip loss time i.e. 25.19 min and melting resistance. Moreover, maximum fat destabilization and overrun in the ice cream manufacturing process was observed in SM2 with the highest overall acceptability score of 8.08 on 9 points hedonic scale. It was found that sodium alginate gel hydrated in milk when added to milk and butter followed by dry ingredients addition forms a superior mix in terms of air cells with strong emulsion boundaries and small ice crystals. Graphical abstract: Image 1 Highlights: A standard ice cream recipe was reformulated by amalgamating ingredient addition order. Water and milk based sodium alginate gels were developed and used for mix development. Physico-chemical properties, sensory, microscopic, and melting characteristics of ice cream samples was studied. Reformulation can yield a mix with high stability and overrun, smaller ice crystals and more destabilized fat.